Jucelino Kubitschek e Salomão: a força de uma ideologia - Soares, Andreia Jordânia Martins (2011)
Brasília, the capital of Brazil, is located in the Midwest of the country, within the red lands of the Cerrado (savanah) of Goiás, and outstands other capitals because of its beautiful monuments, symbols of modern architecture, as recognized on international level. The first chapter analyses the process of moving the capital since the Colonial period of Brazil up to the Republic. It deals with the constitutional aspects which supported the capital transference, as well as all governmental articulation in order to justify the building of a new capital, as fast as possible, on the Central Plateau. The building of Brasilia, as a meta-synthesis of Kubitschek´s (JK) Governance Program, will get supportive as well as contrary reactions. It became a symbol and the most important work of the national development policy. Its construction was a big challenge imposed by JK onto Brazil. The second chapter focuses on Solomon s construction policy, where we can find many elements of unscrupulous struggle for domination, many intrigues and manipulations made by Solomon s group in order to take the throne, usurping the legitimate heir. It stresses the architectonic works ordered by Solomon which form the background of a policy of oppression and domination over Israel and foreign nations. It emphasizes the construction of the Temple, the most important work of the Solomon s Kingdom, which constitutes a strong religious motive in support of the power of the monarch and the whole state apparatus. With the building of the Temple the contractual relationship between the king and the people was reestablished, which gave Solomon the right to charge tribute. The several constructions required an extensive hand labor. Solomon imposes the corvée labor and recruites thousands of workers for his construction projects. The corvée was an enormous exploitation of human labor, imposed especially on the tribes of the North and on foreigners. The third and last chapter speaks about the situation of the workers at the time of Brasilia s construction. It analyses the ideological process behind the transference and the construction of a new capital and how this ideology of national development was spread in so powerful a way that it convinced and gathered thousands of rural workers to the construction place. It analyses also the precarious labor conditions and the backstage reality which confirm the deep spoliation lived by the candangos (the first workers to build Brasilia). At the end, this research establishes a parallel between the Davidic Monarchy and the Juscelino Kubitschek government.